Exploring the misrepresentation of Nigerian women in technical and vocational education in polytechnic institution - Akor, Robert Thomas; Bakar, Ab. Rahim; Hamzah, Azim; Mat Rashid, Abdullah (Australian International Academic Centre, 2014)
Nigerian government is making frantic efforts to drive her economy by laying emphasis on technical and vocational education to enable her compete favorably in the global market. Emphasis of government is in Polytechnic education where skills for self-reliant and economic growth are a priority. However, women are not embracing this opportunity by participating in the program that will equip them with skills and contribute to national development. In all 14 female participants were purposefully selected from Polytechnic. Phenomenological methodology was adopted and data collected were transcribed and analyzed. Results from the study include math/science phobia, perceived social support, and contextual roles among reasons for misrepresentation of women in technical and vocational education. Unless women have increased access to technical and vocational education in order to build diverse technical skills their vulnerability to unemployment and poverty will be on the rise. The findings of this study will guide stakeholders to develop a framework for improving the enrollment of women in this field.